2021
DOI: 10.1111/1759-7714.14265
|View full text |Cite
|
Sign up to set email alerts
|

High GNG4 expression is associated with poor prognosis in patients with lung adenocarcinoma

Abstract: Background: The purpose of this study was to explore the reason for guanine nucleotide binding-protein gamma subunit-4 (GNG4) overexpression and the relationship between GNG4 overexpression and the poor prognosis of lung adenocarcinoma (LUAD) patients. Methods: The genes and phenotypes related to GNG4 expression in patients with lung adenocarcinoma were analyzed by bioinformatics. The phenotype indicated by bioinformatic analysis was confirmed by experiments. Results: GNG4 expression is elevated in lung adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…GNG4 expression was positively correlated with TNM stages, suggesting that GNG4 may be involved in tumour metastasis and progression. The high expression of GNG4 predicted shorter survival in COAD and LUAD, which was consistent with previous studies 16,17,27 . A pan‐cancer immunological correlation of GNG4 aimed to determine cancer types that may benefit from anti‐GNG4 immunotherapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…GNG4 expression was positively correlated with TNM stages, suggesting that GNG4 may be involved in tumour metastasis and progression. The high expression of GNG4 predicted shorter survival in COAD and LUAD, which was consistent with previous studies 16,17,27 . A pan‐cancer immunological correlation of GNG4 aimed to determine cancer types that may benefit from anti‐GNG4 immunotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, hypermethylated GNG4 was found in bladder cancer and glioblastoma 14,15 . Furthermore, high expression of GNG4 has also been associated with the progression of CRC 16 and a variety of malignant phenotypes of lung adenocarcinoma 17 . GNG4 was demonstrated to be the key element of the CRC TMB, which is essential for immune checkpoint inhibitor (ICI) therapy of CRC 18 .…”
Section: Introductionmentioning
confidence: 99%
“…GNG4 is a member of the G-protein family and, similar to PIK3C2G, has been closely associated with PI3K/Akt signaling pathway in HNSCC [ 53 ]. Although GNG4 has been reported to be hypermethylated and down-regulated in bladder cancer [ 54 ], breast cancer [ 55 ], and glioblastoma [ 56 ], other studies have shown that GNG4 expression was significantly up-regulated in lung carcinoma [ 57 ], and colorectal cancer [ 58 ]. More interestingly, in a paper by You et al, GNG4 has been listed as one of the up-regulated genes potentially involved in radioresistance in HNSCC [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…GNG4 was also explored as a downstream target of PSMC2 in gallbladder cancer (GBC) ( Zhu et al, 2021 ). In addition, GNG4 promotes the progression of lung cancer ( Zhou et al, 2022 ). However, rarely studies of GNG4 were discovered in HCC.…”
Section: Discussionmentioning
confidence: 99%